Exploring local attitudes towards current and potential future invasive wasp management in Aotearoa New Zealand - Matthew W. F. Howse; Alan King-Hunt; Ocean Ripeka Mercier; Philip J. Lester (Kōtuitui)
Social support for pest management programs is essential to their success. In this study, we explored stakeholder perceptions of current wasp management and what attempting eradication means for them. Local stakeholders involved in 7 conservation or pest management projects across Aotearoa New Zealand were interviewed. Q-method analysis identified two major perspectives across the participants. A target-driven and ambitious perspective emerged where eradication of invasive wasps was the objective and any control method deemed effective could be used to achieve that goal. Negative impacts of management could be justified by removing the larger negative impact of wasps on the environment. The second perspective identified agreed that wasps must be managed but were characterised as more holistically minded. Control methods perceived to have negative impacts to the wider ecosystem were deemed less acceptable. Education and engagement were highlighted as essential to increase local support for future wasp management. Developing pest management strategies informed by mana whenua is especially crucial, and hapū enabled to draw on their mātauranga Māori may provide new insights into developing effective and acceptable pest management practices. Emphasis not just on technical but social and cultural aspects of wasp eradication and control will be vital for successful wasp management.Glossary of Māori words: Hapū: subtribal group; iwi: tribal group; maramataka: Māori lunar calendar; mātauranga Māori: Māori knowledge systems; mauri: life force or vital essence; taonga: precious thing or treasure; tapu: sacred, restricted or prohibited; te ao Māori: Māori worldview; tohu: a sign or indication; whakapapa: genealogy or line of descent